Neuro-evolução aplicada na conclusão de jogos de plataforma - Chen, Daniel Akio (2022)
Due to the growing number of people consuming electronic games it is inevitable the gaming industry will grow as well. With the increased access to video games, many healthcare professionals have taken advantage of them as tools to support patient care. However, many games are still not used in these procedures because health professionals do not have assessments that provide parameters for deciding whether the level of difficulty of a particular game is appropriate to the profile of the patient being treated. This work presents a game neuro-evolution method, a way to build neural networks for solving and evaluating games, and the steps used to build such a tool.